Diabetes and bacterial infection - Tae-Bong Kang; Yasmin Hisham; Youngmin Lee; Hyunjhung Jhun; Joohee Kim; Soohyun Kim (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2022)
People with diabetes are at increased risk of infection and are worried about biological agents such as bacteria. Particularly, foot infections, urinary tract infections, pneumonia, and skin diseases are due to bacterial infections that make diabetic patients suffer from clinical difficulties. Although antibiotics, one of the bacterial therapies, have been used, the emergence of multidrug-resistant bacteria is now in demand for alternative therapies. Although, many studies reported that antibiotic-resistant for bacterial infections and their rate have increased significantly in the diabetic patient population. Still, there is no report that directly compares the prevalence of antibiotic-resistant infections in diabetes types. In this review, we described the diverse types of diabetes with their bacterial infection and the reported resistance. Generally, diabetic patients are susceptible to vancomycin-resistant enterococcal infections, extended-spectrum β-lactamase-producing intestinal bacteria, carbapenem-resistant intestinal bacteria, and unfermented gram-negative bacilli. Thus, early detection of diabetes and prompt treatment are important to control chronic infections in diabetic patients.